A highly active nickel electrocatalyst shows excellent selectivity for CO2 reduction in acidic media - Iain Aldous (Chemical Science, 2016)
The development of selective electrocatalysts for CO2 reduction in water offers a sustainable route to carbon based fuels and feedstocks. However, molecular catalysts are typically studied in non-aqueous solvents, in part to avoid competitive H2 evolution. [Ni(cyclam)]2+ (1) is one of the few known electrocatalysts that operate in water and 30 years after its report its activity remains a rarely surpassed benchmark. Here we report that [Ni(cyclam-CO2H)]2+ (cyclam-CO2H = 1,4,8,11-tetraazacyclotetradecane-6-carboxylic acid (2)) shows greatly enhanced activity versus1 for CO production. At pHs < pKa of the pendant carboxylic acid a large increase in catalytic activity occurs. Remarkably, despite the high proton concentration (pH 2), 2 maintains selectivity for CO2 reduction and is believed to be unique in operating selectively in such acidic aqueous solutions.